The Use of O Universal Profile Within Hemorrhagic Shock Post-partum Bleeding Patients in Dr. Soetomo General Hospital’s Emergency Installation - Anastasia Pearl Angeli; Soni Sunarso Sulistiawan; Jimmy Yanuar Annas; Pesta Parulian Maurid Edwar (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2022)
Background: Hemorrhagic shock is one of the most common types of shock in trauma patients, and it is defined as acute blood volume loss. One of the causes of hemorrhagic shock is post-childbirth bleeding or post-partum bleeding. The most important management for patients who experience post-partum bleeding is blood transfusions. Type-O blood is known as a universal donor, because someone with type- O blood can transfuse theirs to recipients with blood types other than O. Giving blood transfusions to pos-tpartum bleeding patients is expected to extend their life expectancy, however it cannot be denied that there are quite a several patients who died after receiving transfusions from universal type O blood.Objective: This study aims to determine the profile and effect of universal O use on hemorrhagic shock within post-partum bleeding patients at IGS RSUD Dr. Soetomo Surabaya.Methods: This research was conducted by a descriptive retrospective method by observing the patient's medical record data in the central medical record room of Dr. Soetomo Hospital, Surabaya.Result: There were 17 patients with hemorrhagic shock due to post-partum hemorrhage who received blood transfusions from universal O donors at Dr. Soetomo Surabaya. From the obtained data, the patient age group was dominated by the 28 years old group (23,5%). Transfusion history within patients with the most hemorrhagic shock due to post-partum bleeding were patients who received transfusions with packed red cell (PRC) O + (76,5%). As for transfusion reactions that occur within patients, there are no data on transfusion reactions.Conclusion: The 28 years old group was the largest one that received transfusions from the universal group O blood. History transfusion of hemorrhagic shock due to post-partum bleeding patients shows that most of them are those who received PRC O + transfusions. There are no data regarding the transfusion reactions which occurred in these patients.